Perlindungan Hukum Terhadap Konsumen Kosmetik Krem Wajah Tanpa Notifikasi BPOM - Hikmawati Ribi (Jurnal Restorative, 2023)
Abstract                   The purpose of this research is to find out and analyze the legal protection for cosmetic consumers of face cream without BPOM notification and to find out and analyze the responsibility of business actors for the circulation of cosmetics that are detrimental to consumers of cosmetic face cream without BPOM notification. The research method is normative juridical research, namely research conducted by examining literature or secondary data as the basis for research by conducting a search of regulations and literature related to the problem under study. Analysis of the data used is by identifying and classifying existing data and compiling it systematically.                  Based on the results of the research conducted, the authors conclude that the legal protection obtained by cosmetic consumers of face cream without BPOM notification is very clearly regulated in Law no. 8 Consumer Protection 1999, Health Law no. 36 of 2009. Responsibilities of Business Actors for the Circulation of Face Cream Cosmetics without BPOM Notification which are Harmful to Consumers In article 19 paragraph 1 of Law Number 8 of 1999 concerning consumer protection "Business actors are responsible for providing compensation for damage, pollution and/or consumer losses as a result of consuming goods and/or services produced or traded. As compensation that is charged to business actors in accordance with the loss, damage, or pollution suffered by consumers after using face cream without BPOM notification.Keywords: Consumer protection, face cream, notification